2004
DOI: 10.1017/s1464793103006420
|View full text |Cite
|
Sign up to set email alerts
|

Vision in the deep sea

Abstract: The deep sea is the largest habitat on earth. Its three great faunal environments--the twilight mesopelagic zone, the dark bathypelagic zone and the vast flat expanses of the benthic habitat--are home to a rich fauna of vertebrates and invertebrates. In the mesopelagic zone (150-1000 m), the down-welling daylight creates an extended scene that becomes increasingly dimmer and bluer with depth. The available daylight also originates increasingly from vertically above, and bioluminescent point-source flashes, wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
403
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 360 publications
(411 citation statements)
references
References 138 publications
5
403
1
2
Order By: Relevance
“…That same study in addition found (as was shown here) that the eyes of the four Arctic charr morphs tended to become relatively smaller as the fish grew larger. Deep‐water morphs of whitefish have also been found to have relatively big eyes (Siwertsson, Knudsen, Adams, Præbel, & Amundsen, 2013) as also found in deep‐water adapted taxa living in the sea (Warrant & Locket, 2004). …”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…That same study in addition found (as was shown here) that the eyes of the four Arctic charr morphs tended to become relatively smaller as the fish grew larger. Deep‐water morphs of whitefish have also been found to have relatively big eyes (Siwertsson, Knudsen, Adams, Præbel, & Amundsen, 2013) as also found in deep‐water adapted taxa living in the sea (Warrant & Locket, 2004). …”
Section: Discussionmentioning
confidence: 86%
“…The LO‐morph in Lake Skogsfjordvatn was less diverged genetically from the PP‐ and PB‐morphs than the PP‐ and PB‐morphs were from each other, suggesting that the divergence in allometric processes follows another genetic trajectory than neutral genetic divergence. This is most likely because of similar adaptation to the deep‐water environment of the PB‐ and PP‐ morphs related to morphological adaptations to low temperature and light conditions (Luk et al., 2016; Warrant & Locket, 2004) and to less need for maneuverability in a less complex habitat structure.…”
Section: Discussionmentioning
confidence: 99%
“…Banked retinas allow maximum absorption of the incoming light [2] and are thus an adaptation for increased sensitivity in the dim light of the deep sea. The escolar have between six and eight layers of rods in their retinas (figure 3b).…”
Section: (B) Retinal Sections and Organization Of Photoreceptors In Tmentioning
confidence: 99%
“…At great depths in the ocean it can be totally dark, a darkness broken only by rare and unpredictable sparks of bioluminescence produced by animals themselves. Nonetheless, for the immense variety of animals that live in nocturnal and deep-sea habitats (figure 1), vision plays a surprisingly important role in the tasks of daily life [16][17][18][19][20][21].…”
Section: The Dimmest Habitats On the Earthmentioning
confidence: 99%